How does mind-wandering affect distractor suppression? - Zhang, Han; Miller, Kevin F.; Jonides, John (Visual Cognition)
The current study examined whether the suppression of overt attention to a salient distractor requires attentional resources. In a feature-search task, participants searched for a constant shape among different shapes while ignoring a uniquely coloured distractor. Trial-by-trial fluctuations in attentional resources were assessed via thought probes that elicited mind-wandering reports and via pre-trial pupil sizes. The results show that initial eye movements to the distractor were suppressed regardless of the availability of attentional resources. However, when mind-wandering, the presence of the distractor prolonged target looking time. Thus, the initial deployment of overt attention in this task does not require attentional resources and can proceed automatically, presumably due to strong selection history. Nonetheless, the distractor might still disrupt later processing stages, an effect exacerbated by mind-wandering. These results also suggest that initial eye movements do not fully reflect the extent of distractor interference during the entire course of visual search.